Comparison of V[Combining Dot Above]O2peak and V[Combining Dot Above]O2max at Different Sampling Intervals in Collegiate Wrestlers. Issue 10 (October 2021) - Sell, Katie M.; Ghigiarelli, Jamie J.; Prendergast, James M.; Ciani, Gioia J.; Martin, Jacob; Gonzalez, Adam M.
Abstract : Abstract: Sell, KM, Ghigiarelli, JJ, Prendergast, JM, Ciani, GJ, Martin, J, and Gonzalez, AM. Comparison of V[Combining Dot Above]O2 peak and V[Combining Dot Above]O2 max at different sampling intervals in collegiate wrestlers. J Strength Cond Res 35(10): 2915–2917, 2021—The purpose of this study was to determine the difference in the highest oxygen uptake (V[Combining Dot Above]O2 peak) achieved during a maximal effort graded exercise test (GXT) in 20 NCAA Division I male wrestlers using breath-by-breath (BbB) values to the maximal uptake averaged across different time- and breath-based oxygen consumption sampling intervals (V[Combining Dot Above]O2 max). Given the need for aerobic fitness and anaerobic power in wrestling, the accurate determination of V[Combining Dot Above]O2 max is imperative if it is to be used to identify current aerobic fitness and consequently guide sport-specific training programs to address weaknesses in this area. Each subject completed a cycle ergometer GXT during which BbB data were collected via indirect calorimetry and V[Combining Dot Above]O2 peak determined as the highest value. V[Combining Dot Above]O2 max was considered as the average value of 3-s, 5-s, 10-s, 20-s, and 30-s sampling, and 3-b, 7-b, and 11-b sampling during the GXT. Results show that the BbB V[Combining Dot Above]O2 peak was significantly higher than the 5-s, 10-s, 20-s, 30-s, and 11-b ( p < 0.05). The 3-b V[Combining Dot Above]O2 max was significantly higher than the 20-s and 30-s V[Combining Dot Above]O2 max values ( p < 0.05). The underestimation of V[Combining Dot Above]O2 peak for each time-based interval sampling approach compared with BbB V[Combining Dot Above]O2 peak is consistent with previous research, but the comparison of BbB data to breath-based interval sampling has not been widely addressed in prior research. The use of a 7-b sampling interval for the determination of V[Combining Dot Above]O2 max may be a promising approach to minimize the systematic errors associated with BbB or less frequent sampling intervals, but future research is needed to further support its application with elite athletic populations such as those in the current study.